Prävention und Behandlung der Kachexie: Bewegungs- und Ernährungstherapie = Prevention and treatment of cachexia : exercise and nutritional therapy - Wilms, Britta; Wiskemann, Joachim (Der Internist, 2016)
BackgroundCachexia is a multifactorial and complex syndrome characterized by progressive functional impairment and ongoing loss in quality of life, which lead to a deterioration of the prognosis for affected patients. The prevalence of cachexia can be very high and is up to 80 % in patients with malignant tumors.ObjectiveThe aim of the study was to assess the relevance of exercise and nutrition in the prevention and therapy of cachexia.MethodsAn evaluation of the current literature on exercise and nutritional therapy in patients with cachexia or with advanced stage diseases where a high prevalence of cachexia is probable, was carried out.ResultsThere is a lack of scientific evidence for the benefits of exercise in cachexia. A major problem of relevant studies was that cachexia was frequently not defined according to valid criteria; however, data indicate a benefit of exercise training in patients with advanced diseases associated with a high prevalence of cachexia. A solely nutritional intervention and dietary counselling seem to be of minimal benefit. The administration of omega 3 fatty acids is controversially discussed.ConclusionAlthough there is a lack of data on the effects of exercise and nutritional therapy in cachexia, there is evidence for the benefits. The present data indicate the necessity for the use of a multimodal treatment including exercise, nutritional and pharmacological therapy in cachexia. There is a great necessity for prospective studies
Gesehen am 31.08.2017